Anti-Ro52 Autoantibodies Are Related to Chronic Graft-vs.-Host Disease After Allogeneic Hematopoietic Stem Cell Transplantation - Yang, Kaibo; Chen, Yanqiu; Qi, Hanzhou; Ye, Yiling; Fan, Zhiping; Huang, Fen; Zhang, Haiyan; Suo, Yuan; Liu, Qifa; Jin, Hua (Frontiers in Immunology, 2020)
Chronic graft-versus-host disease (cGVHD) remains a major cause of morbidity and mortality after allogeneic hematopoietic stem cell transplantation (allo-HSCT). Previous studies have shown that autoantibodies play an important role in the development of cGVHD. Anti-nuclear autoantibodies (ANA) are the most frequently detected autoantibodies in patients with cGVHD, but the role of anti-Ro52 autoantibodies (anti-Ro52) in cGVHD remains largely unknown. In this study, we analyzed autoantibodies from 84 patients after allo-HSCT, including 42 with active cGVHD and 42 without cGVHD. Autoantibodies were found in 36 (42.9%) patients. Among these autoantibody-positive patients, 28 (77.8%) patients had active cGVHD. The most frequent autoantibodies in patients with active cGVHD were ANA (50.0%), anti-Ro52 (28.6%) and anti-mitochondrial autoantibodies type 2 (4.8%). We further explored the role of anti-Ro52 in the development of cGVHD. Patients with active cGVHD had higher anti-Ro52 levels than patients without cGVHD (P < 0.05). The increases of anti-Ro52 levels were more signiﬁcant in patients with moderate/severe cGVHD compared to those of patients without cGVHD (P < 0.05). Stratified and multivariable logistic regression analysis demonstrated that moderate/severe cGVHD was an independent risk factor for the levels of anti-Ro52 (P < 0.01). Moreover, the anti-Ro52 levels were highly correlated with the levels of B cell-activating factor (BAFF) and IgG1 antibodies. Our study demonstrates that anti-Ro52 is associated with the development of cGVHD. The increased levels of anti-Ro52 were associated with higher levels of BAFF and IgG1 antibodies, suggesting a mechanistic link between elevated anti-Ro52 levels and aberrant B cell homeostasis. Anti-Ro52 can be used to diagnose cGVHD and monitor cGVHD progression.